2020
DOI: 10.1111/joa.13318
|View full text |Cite
|
Sign up to set email alerts
|

Are endocasts reliable proxies for brains? A 3D quantitative comparison of the extant human brain and endocast

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…The endocranium is a reliable proxy for the brain in a range of craniates, including mammals (e.g. Dumoncel et al, 2020; Early et al, 2020). Relative masseter size was calculated as masseter volume divided by endocranial volume.…”
Section: Methodsmentioning
confidence: 99%
“…The endocranium is a reliable proxy for the brain in a range of craniates, including mammals (e.g. Dumoncel et al, 2020; Early et al, 2020). Relative masseter size was calculated as masseter volume divided by endocranial volume.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it was shown recently that scalp curvature is not related to brain gyrification [3]. However, very few such studies have been carried out on the links between cortical morphology and the internal interface of the skull, which gives rise to the endocasts of paleoanthropology [4]. This is an important topic addressed in this study.…”
Section: Introductionmentioning
confidence: 90%
“…However, the correspondence between these limited records of convolutional patterns and details of the surface of the brain remains to be demonstrated in modern humans. A few pioneer studies have considered this problem [4,44]. Moreover, it is necessary to develop new tools for the automatic and reliable determination of the endocranial sulci [45].…”
Section: Does the Endocast Reflects The Brain?mentioning
confidence: 99%
“…The analysis of endocranial morphology using 3D digital models generated from computer tomography (i.e., endocasts) allows us to include a larger number of species in the comparative analysis. Even though the endocasts do not provide detailed information about all gyri and sulci or subcortical regions, the inner surface of the skull is a good proxy for global asymmetry of the brain (Fournier et al 2011;Dumoncel et al 2021). Previous studies have shown that the analysis of endocast shape allows the quantification of external brain morphology because it represents a good proxy for describing correlated changes in relative size and position of brain lobes (Aristide et al 2016;Neubauer et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the analysis of endocast shape allows the quantification of external brain morphology because it represents a good proxy for describing correlated changes in relative size and position of brain lobes (Aristide et al 2016;Neubauer et al 2020). In this way, endocasts are a valuable source of information being increasingly used for studying the evolution of the brain in extinct and extant species (Neubauer et al 2010;Watanabe et al 2019;Dumoncel et al 2021;Early et al 2020). Particularly for the latter, endocasts are used because it is not always possible to collect specimens under the conditions required to preserve the soft tissues, and in some cases the capture of wild specimens and endangered species is not allowed.…”
Section: Introductionmentioning
confidence: 99%